2015
DOI: 10.4172/2161-0681.1000224
|View full text |Cite
|
Sign up to set email alerts
|

A Giant Primary Clear Cell Hepatocellular Carcinoma in a Young Woman without Cirrhosis

Abstract: Primary clear cell carcinoma of the liver (PCCCL) is an uncommon variant of hepatocellular carcinoma, usually occurring in older patients with longstanding cirrhosis. We report a case of a giant PCCCL rupturing in a young woman without cirrhosis.A 29 year-old female who presented with a three month history of abdominal pain, nausea, vomiting, food intolerance, and unintentional weight loss, was found to have gastric varices and a large liver mass measuring 22.8 cm × 17.8 cm × 13.8 cm. The tumor was comprised o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, the relationship between obesity and CCHCC is not well understood. A study by Ko et al [11] reported a CCHCC in a young woman with obesity, type II diabetes mellitus, and hyperlipidemia. Another case by Orikasa et al [12] described a lipid-rich CCHCC in a slightly overweight patient with non-alcoholic steatohepatitis and diabetes mellitus.…”
mentioning
confidence: 99%
“…However, the relationship between obesity and CCHCC is not well understood. A study by Ko et al [11] reported a CCHCC in a young woman with obesity, type II diabetes mellitus, and hyperlipidemia. Another case by Orikasa et al [12] described a lipid-rich CCHCC in a slightly overweight patient with non-alcoholic steatohepatitis and diabetes mellitus.…”
mentioning
confidence: 99%